The influence of powder bed porosity variations on the filling of hard gelatin capsules by a dosator system - Woodhead, Philip John (1980)
The weight variation of gelatin capsules filled by a dosator-type machine has several possible causes, one of which, the presence of density variations within the powder feed bed, has been evaluated, using a number of particle size fractions of material. Existing theories suggested that the bulk density, or porosity of a powder bed depends on the velocity and intensity of deposition of the particles, together with the properties of the powder. Experiments with lactose confirmed this, indicating in particular that low velocity deposition encourages the formation of regions of relatively high porosity. The application of vibration, especially in a vertical direction, proved effective in reducing the porosity of powder packings, and optimum frequency and acceleration appeared to be largely independent of particle size. A system was developed for detecting porosity variations within powder beds, using the technique of gamma-ray attenuation, the principle being that the reduction in intensity of a Gamma-ray beam traversing a powder bed is a function of local porosity. The observed linear attenuation coefficient of lactose was found to be a function of porosity, for reasons not fully established, hence a calibration expression for the attenuation coefficient was proposed, and was used in subsequent local porosity determinations. The radial distribution of porosity within cylindrical samples of lactose, prepared under various conditions, was studied, and a means of presenting such distributions pictorially was developed. The influence of deposition method, and applied vibration, on the uniformity, of such packings, was clearly demonstrated. A semi-automatic dosator-type capsule filling machine was used to evaluate the relationship between powder feed bed porosity variations and capsule fill weight variation. The results indicated that in the case of lactose, the influence of porosity variations, of the order of magnitude encountered, tends to be masked by other phenomena affecting the filling process.